Self-care of elderly people with diabetes mellitus and the nurse-patient interpersonal relationship - Gerlania Rodrigues Salviano Ferreira; Lia Raquel de Carvalho Viana; Cláudia Jeane Lopes Pimenta; Cleane Rosa Ribeiro da Silva; Tatiana Ferreira da Costa; Jacira dos Santos Oliveira; Kátia Neyla de Freitas Macedo Costa (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To analyze the self-care activities of elderly people with diabetes mellitus and its correlation with the nurse-patient interpersonal relationship. Methods: Cross-sectional quantitative study, with 144 elderly people followed up in Family Health Units, with data collected by the Diabetes Self-Care Activities Questionnaire and Interpersonal Relationship Questionnaire in Nursing Care, being analyzed by descriptive and inferential statistics. Results: There was a greater accomplishment of the activities Take insulin injections as recommended (6.74), Take diabetes medications as recommended (6.55) and Take the indicated number of diabetes pills (6.52). The interpersonal relationship showed moderate effectiveness (80.6%). The correlation between self-care with diabetes and interpersonal relationships showed a positive and significant value in the dimension Specific feeding. Conclusion: The effectiveness of the interpersonal relationship in nursing care resulted in greater compliance with activities related to specific food.